The extent of urban Green Collar employment, its contribution to poverty alleviation and potential for growth in the Eastern Cape, South Africa - King, Andrew (Rhodes University, Faculty of Science, Department of Environmental Science, 2019)
The aim of this research was to investigate the job provisioning benefits of urban green space (GS), the ability of these jobs to alleviate poverty amongst poor urban households, as well as the potential to increase the number of Green Collar (GC) jobs. According to Lal et al. (2010), Roy et al. (2012) and others, environmental employment or GC jobs, represent the very synergy between social, economic and environmental resilience and sustainability, and have the ability to provide an additional range of goods and services. Data was collected from 12 towns and cities in the Eastern Cape of South Africa, all varying in population, town size and geographic location. Structured employer, employee and resident interviews were used to collect data, which pertained to a number of employment characteristics and employee living conditions. Throughout the sample, 19 different types of jobs were identified, and a total of 17 429 GC employees were counted, sharing a total of approximately R503 million in annual wages. Some GC employees were found to still be in a position of poverty despite employment, while others enjoyed a higher standard of living as a result, although this was largely dependent on the extent of wages and other household and employment attributes. Using lessons learnt from previous chapters, a number of data sources and a creative approach, the potential for growth and improvement in the urban GC sector was discussed, and the way forward involves private, public, informal and civil sector participation and innovation; which will not only enhance environmental and social ecosystem services, but also provide meaningful employment opportunities to the otherwise impoverished. Urban GC jobs should be widely viewed as a useful tool in achieving social, environmental and economic prosperity in urban landscapes (Bowen and Kuralbayeva, 2015).
Keywords: Economic development -- Environmental aspects -- South Africa -- Eastern Cape; Poverty prevention -- South Africa -- Eastern Cape; Job creation -- South Africa -- Eastern Cape; Urban ecology (Sociology) -- South Africa -- Eastern Cape; Urban poor -- Employment -- South Africa -- Eastern Cape; Clean energy industries -- Employment -- South Africa -- Eastern Cape; Renewable energy sources -- Government policy -- South Africa -- Eastern Cape; Land use, Urban -- South Africa -- Eastern Cape; Open spaces -- Environmental aspects -- South Africa -- Eastern Cape